2018
DOI: 10.1021/acs.jpcb.7b11763
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Energy Landscape of the Y16F Mutant of the Chlorobium tepidum Fenna–Matthews–Olson (FMO) Complex: High Resolution Spectroscopic and Modeling Studies

Abstract: We report high-resolution (low-temperature) absorption, emission, and nonresonant/resonant hole-burned (HB) spectra and results of excitonic calculations using a non-Markovian reduced density matrix theory (with an improved algorithm for parameter optimization in heterogeneous samples) obtained for the Y16F mutant of the Fenna-Matthews-Olson (FMO) trimer from the green sulfur bacterium Chlorobium tepidum. We show that the Y16F mutant is a mixture of FMO complexes with three independent low-energy traps (locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
(122 reference statements)
4
12
0
Order By: Relevance
“…In conclusion, we have demonstrated that the effect of the protein scaffold in pigment–protein complexes is not limited to variations of the site energies of the pigments, as largely documented in the literature, , ,, but that the establishment of specific and directional interactions can have very strong consequences for the electronic coupling and for the ultrafast dynamics of pigment–protein complexes as well. This is a particularly important finding because beyond having characterized this behavior in the WSCP, it implies the possibility of tuning the photophysics and the transport properties of multichromophores by engineering specific interactions with the surroundings.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…In conclusion, we have demonstrated that the effect of the protein scaffold in pigment–protein complexes is not limited to variations of the site energies of the pigments, as largely documented in the literature, , ,, but that the establishment of specific and directional interactions can have very strong consequences for the electronic coupling and for the ultrafast dynamics of pigment–protein complexes as well. This is a particularly important finding because beyond having characterized this behavior in the WSCP, it implies the possibility of tuning the photophysics and the transport properties of multichromophores by engineering specific interactions with the surroundings.…”
supporting
confidence: 56%
“…Biological systems, such as light-harvesting complexes, are characterized by optimized structures where the protein scaffold acts on the active molecules, finely tuning their surroundings and modulating their properties and functionalities. Numerous studies have addressed the contributions of individual amino acids to modulating the spectroscopic properties of bound chromophores, recognizing that they may act either by determining their 3D arrangement, thus affecting their interchromophore interactions, or by modifying their site energy. In several instances, these chromophore tunings have been achieved by means of hydrogen (H) bonds. , ,, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen bonding between the carbonyl groups of (B)Chl pigments and the neighboring amino acid residues in light‐harvesting proteins is an important factor in fine‐tuning of the absorption energies of (B)Chl pigments (8–11). Such interactions have been extensively studied for the 3‐acetyl group of BChl a in bacterial light‐harvesting proteins, such as light‐harvesting complex 1 (12–17), light‐harvesting complex 2 (LH2) (12,18–22), light‐harvesting complex 3 (12,19,23) and Fenna–Matthews–Olson proteins (24–26).…”
Section: Introductionmentioning
confidence: 99%
“…This latter role is of paramount relevance for proteins involved in the photosynthetic process, as they need to bind numerous pigments, such as chlorophylls (Chls), in a precise three-dimensional arrangement to effectively harvest and utilize incoming light 6 . Numerous mutational studies have been performed on photosynthetic proteins, that helped to highlight the role of individual H-bonds in determining the spectroscopic properties of the bound pigments 714 . Beside modulating the properties of the bound Chls 710,15 , the presence of an appropriate H-bond donor in close proximity to the C-7 1 atom of the Chls (see Fig.…”
Section: Introductionmentioning
confidence: 99%